Cooperative Binding of the Class I Major Histocompatibility Complex Cytoplasmic Domain and Human Immunodeficiency Virus Type 1 Nef to the Endosomal AP-1 Complex via Its μ Subunit - Noviello, Colleen M. (American Society for Microbiology (ASM), 2008)
Human immunodeficiency virus type 1 Nef provides immune evasion by decreasing the expression of major histocompatibility complex class I (MHC-I) at the surfaces of infected cells. The endosomal clathrin adaptor protein complex AP-1 is a key cellular cofactor for this activity, and it is recruited to the MHC-I cytoplasmic domain (CD) in the presence of Nef by an uncharacterized mechanism. To determine the molecular basis of this recruitment, we used an MHC-I CD-Nef fusion protein to represent the MHC-I CD/Nef complex during protein interaction assays. The MHC-I CD had no intrinsic ability to bind AP-1, but it conferred binding activity when fused to Nef. This activity was independent of the canonical leucine-based AP-binding motif in Nef; it required residue Y320 in the MHC-I CD and residues E62-65 and P78 in Nef, and it involved the μ but not the γ/σ subunits of AP-1. The impaired binding of mutants encoding substitutions of E62-65 or P78 in Nef was rescued by replacing the Y320SQA sequence in the MHC-I CD with YSQL, suggesting that Nef allows the YSQA sequence to act as if it were a canonical μ-binding motif. These data identify the μ subunit of AP-1 (μ1) as the key target of the MHC-I CD/Nef complex, and they indicate that both Y320 in the MHC-I CD and E62-65 in Nef interact directly with μ1. The data support a cooperative binding model in which Nef functions as a clathrin-associated sorting protein that allows recognition of an incomplete, tyrosine-based μ-binding signal in the MHC-I CD by AP-1.